The ‘Next People’: And the Zombies Shall Inherit the Earth - Carrington, Victoria (Generation Z, 2015)
On Halloween night 2014 I stood with thousands of others along the side of a large boulevard in Amsterdam. There was an excited buzz rippling through the crowd and young children zipped in and out, threading their way around their parents and friends, vying for the best viewing locations. Their cries and laughter filled the air alongside the adult conversation and the sound of phones ringing as people attempted to find each other in the crowd. We were all waiting with mounting excitement for the annual Halloween Parade. It was running late. Heads turned down the street, cameras and phones at the ready, watching for any sign that the parade was arriving. Expectation hung in the air. Finally … music. And then a truck disguised as a giant metal dragon belching smoke and music lurched into view, followed by a slow moving phalanx of participants, all in Halloween costumes. Some of the walkers were waving at the crowd, others were ignoring us, while still others lunged at unsuspecting individuals with threatening roars and grimaces. An armada of decorated vehicles, flanked by phalanxes of monsters and ghouls moved slowly along the street.